2003
DOI: 10.1249/01.mss.0000099087.96549.96
|View full text |Cite
|
Sign up to set email alerts
|

Effect of School Age Sports on Leisure Time Physical Activity in Adults: The CORDIS Study

Abstract: Organized school age sporting activities influenced future LTPA in this cohort. Attempts to promote these activities may lead to increased levels of LTPA in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
12

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 22 publications
0
35
1
12
Order By: Relevance
“…In a cohort of male workers in Israel, Kraut et al found an odds ratio of 3.55 (95% CI: 2.97; 4.23) for those engaged in organized school age sport activities compared with those who did not. 13 The different magnitude of the relative risks between the present study and Kraut's can be explained by the fact that their definition of physical activity in adolescence required at least 12 months of practice, while the present study used a six-month period. It is reasonable to believe that the longer the minimum period established to consider individuals as active in adolescence, the higher the effect on the level of physical activity in adulthood.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In a cohort of male workers in Israel, Kraut et al found an odds ratio of 3.55 (95% CI: 2.97; 4.23) for those engaged in organized school age sport activities compared with those who did not. 13 The different magnitude of the relative risks between the present study and Kraut's can be explained by the fact that their definition of physical activity in adolescence required at least 12 months of practice, while the present study used a six-month period. It is reasonable to believe that the longer the minimum period established to consider individuals as active in adolescence, the higher the effect on the level of physical activity in adulthood.…”
Section: Discussioncontrasting
confidence: 57%
“…21 In addition, physical activity in adolescence has been studied as a possible predictor of levels of adult activity. 4,10,12,13,19 The literature shows a non-consistent effect of adolescent physical activity on adult activity behavior. Most studies found weak but significant tracking values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estratégias efetivas de combate ao sedentarismo na adolescência são necessárias, pois além de afetar mais da metade dos jovens, o sedentarismo nessa faixa etária é um fator de risco para inatividade física na idade adulta 3,4 . …”
Section: Materiais E Métodosunclassified
“…A prática adequada de atividade física na adolescência traz vários benefícios para a saúde fí-sica e mental, seja por meio de uma influência direta sobre a morbidade na própria adolescência ou por uma influência mediada pelo ní-vel de atividade física na idade adulta 1,2,3,4 . Embora a maioria das doenças associadas ao sedentarismo somente se manifeste na vida adulta, é cada vez mais evidente que seu desenvolvimento se inicia na infância e adolescência 5 .…”
Section: Introductionunclassified